Numerical simulation of hydrodynamics of ocean-observation-used remotely operated vehicle - Zhang, Dapeng; Zhao, Bowen; Zhang, Yi; Zhou, Nan (Frontiers in Marine Science, 2024)
Remotely operated vehicle is the most widely used underwater robot and can work safely and steadily in complex environments compared to autonomous underwater vehicle and other types. It has obvious advantages in operation time and plays a significant function in marine engineering equipment. Hydrodynamic coefficients are the coefficients of ROV motion equation. In order to simulate the motion and predict the performance of a ROV, the hydrodynamic coefficients must be determined first. The motion mathematical model of remotely operated vehicles is also established, and the hydrodynamic dynamics of the vehicles are simulated using the finite volume method by combining overset mesh technology and governing equations. Finally, a simulation and verification of the standard model SUBOFF model and the calculation process’s dependability are also conducted. The primary hydrodynamic coefficients of the ROV were derived through the simulation data fitting process. The results showed that the ROV’s asymmetry results in an obvious disparity in pressure resistance between the forward and backward sailing, ascending and descending motions, and this disparity becomes significantly greater as the velocity increases. This method confirmed the accuracy of the hydrodynamic simulation computation of the remotely operated vehicle and served as a guide for the maneuverability and design of the vehicle.